Contribution of Islam to International Humanitarian Law - Erwin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The current humanitarian law is based on the experiences of Western countries during wars in Europe, so its formation is influenced by European politics. Meanwhile, Islam, because it was formed based on the customs of the ancient Arab people who fought on land. Therefore, it is very important to know the principles, systems, values, and foundations related to Islam's contribution to the development of international humanitarian law. This research is a type of normative legal research. Islam's contribution to International Humanitarian Law in two main aspects: Humanitarian Law related to general provisions concerning war and peace, and specifically related to prisoners of war, among other things.